The influence of the implementation of CSR on business strategy: An empirical approach based on Cameroonian enterprises - Boubakary; Doumagay Donatienne Moskolaï (Arab Economic and Business Journal, 2016)
In Cameroon, the debate on CSR is now ubiquitous in the speeches of those from the business community as well as the public authorities, rather than by the academic researchers. This article focuses on a study conducted on the Cameroonian enterprises analyzing the influence of the implementation of CSR in business strategy. We will adopt in this study a hypothetical-deductive approach and the questionnaire is the data collection tool. We will conduct our investigation among companies in Cameroon. A representative sample of 126 companies, whose employees were briefed a questionnaire regarding the policies of their companies, was used to study CSR and its strategy. The results of the study show that the implementation of a CSR approach influenced, positively and significantly, innovation, reputation and differentiation of the enterprise.
Keywords: 650; CSR; Strategy; Enterprises